Evaluation of the labor performance of the public servants with appointment in provisional nature: a theoretical review and of legality. (2015)
This paper investigates epistemological, technical and legal affairs about specific instruments application to performance management of public servants with provisional appointment in Executive Branch of Public Authority entities in Colombia. They’re not theoreticians, constitutional and legal arguments which support that performance management is limited by relationship between public servants and Public Administration. Legal framework that regulates civil service doesn’t establish exceptions about performance management.